1981
DOI: 10.1016/0022-3115(82)90706-1
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature fatigue life of type 316 stainless steel containing irradiation induced helium

Abstract: Specimens of 20^-cold-vorked AISI type 316 stainless steel were irradiated In the High Flux Isnt *>r»o R*-.i<"tf>r ('tiy'.ii) .it 550 °C to a aiKimum darr, i;»e level of 15 dpa and a transmit at ion proi.ur.fi h.' I i» J ~ i.'vel :>f d2o ji, ppm-r'ul 17 reversed st r.iin control 1od fat i ,MIC tests w Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…6, the fracture mode of the irradiated specimen fatigue-tested with De t of 0.5% was found to be a channel fracture. Channel fracture [15][16][17] and similar cleavage fracture [18,19] were reported after fatigue tests at De t of about 0.5% in irradiated austenitic stainless steels. In martensitic steels tested by cyclic stress, however, channel fracture has not been reported previously.…”
Section: Discussionsupporting
confidence: 62%
“…6, the fracture mode of the irradiated specimen fatigue-tested with De t of 0.5% was found to be a channel fracture. Channel fracture [15][16][17] and similar cleavage fracture [18,19] were reported after fatigue tests at De t of about 0.5% in irradiated austenitic stainless steels. In martensitic steels tested by cyclic stress, however, channel fracture has not been reported previously.…”
Section: Discussionsupporting
confidence: 62%
“…However, it is possible to discuss the irradiation effects on fatigue life. Some authors [5][6][7] report that fatigue life is reduced by irradiation. On the other hand, Puzzolante [8] concluded that there is little or no effect of irradiation on the fatigue life.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data on the fatigue life of irradiated austenitic stainless steels [5][6][7][8], with all of the data obtained by axial strain fatigue tests. There are no data on bend-fatigue life of irradiated specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The situation can be quite different in the case of fusion devices where ICFRs and the next generation of tokamaks are expected to employ cyclic operation, [99,100];. and where very high helium production rates are expected in addition to the atomic displacements.…”
Section: Fatiguementioning
confidence: 99%